PENGARUH DIFERENSIASI PRODUK TERHADAP KEPUASAN KONSUMEN PADA JASUKE CIKARASA LANGSA - febi febi; Yulina Astuti; Muhammad Zulkarnain; Mukarramah (FEBI IAIN Langsa, 2019)
This study aims to determine the effect of product differentiation on consumer satisfaction on Jasuke Cikarasa Langsa, and how much inﬂ uence the product differentiation on customer satisfaction on Jasuke Cikarasa Langsa. The method used is a quantitative method. The population in this study were all consumers who bought Jasuke Cikarasa Langsa. Implemented by distributing questionnaires to 96 respondents. Data analysis techniques in this study used simple linear regression by looking at the coefﬁ cient of determination, correlation coefﬁcient and F test. The results showed that there was a signiﬁ cant inﬂ uence between product differentiation variables and customer satisfaction. From the calculation of the F test it is known that the F count = 82.088 with a signiﬁ cance level of 0.000 <0.05. Product differentiation has a coefﬁcient of determination of 0.466. It can be concluded that the product differentiation variable inﬂ uences consumer satisfaction on Jassuke Cikarasa Langsa.